Molecular Mechanisms of Laparoscopic Ovarian Drilling and Its Therapeutic Effects in Polycystic Ovary Syndrome - Seow, Kok-Min (Int J Mol Sci, 2020)
Polycystic ovary syndrome (PCOS) is a common endocrinopathy, characterized by chronic anovulation, hyperandrogenism, and multiple small subcapsular cystic follicles in the ovary during ultrasonography, and affects 5–10% of women of reproductive age. PCOS is frequently associated with insulin resistance (IR) accompanied by compensatory hyperinsulinemia and, therefore, presents an increased risk of type 2 diabetes mellitus (DM). The pathophysiology of PCOS is unclear, and many hypotheses have been proposed. Among these hypotheses, IR and hyperandrogenism may be the two key factors. The first line of treatment in PCOS includes lifestyle changes and body weight reduction. Achieving a 5–15% body weight reduction may improve IR and PCOS-associated hormonal abnormalities. For women who desire pregnancy, clomiphene citrate (CC) is the front-line treatment for ovulation induction. Twenty five percent of women may fail to ovulate spontaneously after three cycles of CC treatment, which is called CC-resistant PCOS. For CC-resistant PCOS women, there are many strategies to improve ovulation rate, including medical treatment and surgical approaches. Among the various surgical approaches, one particular surgical method, called laparoscopic ovarian drilling (LOD), has been proposed as an alternative treatment. LOD results in an overall spontaneous ovulation rate of 30–90% and final pregnancy rates of 13–88%. These benefits are more significant for women with CC-resistant PCOS. Although the intra- and post-operative complications and sequelae are always important, we believe that a better understanding of the pathophysiological changes and/or molecular mechanisms after LOD may provide a rationale for this procedure. LOD, mediated mainly by thermal effects, produces a series of morphological and biochemical changes. These changes include the formation of artificial holes in the very thick cortical wall, loosening of the dense and hard cortical wall, destruction of ovarian follicles with a subsequently decreased amount of theca and/or granulosa cells, destruction of ovarian stromal tissue with the subsequent development of transient but purulent and acute inflammatory reactions to initiate the immune response, and the continuing leakage or drainage of “toxic” follicular fluid in these immature and growth-ceased pre-antral follicles. All these factors contribute to decreasing local and systemic androgen levels, the following apoptosis process with these pre-antral follicles to atresia; the re-starting of normal follicular recruitment, development, and maturation, and finally, the normalization of the “hypothalamus–pituitary–ovary” axis and subsequent spontaneous ovulation. The detailed local and systematic changes in PCOS women after LOD are comprehensively reviewed in the current article.